Fungal phylogenetics and phylogenomics - Townsend, Jeffrey P.; Wang, Zheng (Advances in genetics, 2017)
Fungal Phylogenetics and Phylogenomics, Volume 99, the latest release in the Advances in Genetics series, presents users with new chapters that delve into such topics as the Advances of fungal phylogenomics and the impact on fungal systematics, Data crunching for fungal phylogenomics: insights into data collection and phylogenetic inference based on genome data for fungi, Genomic and epigenomic traits of emerging fungal pathogens, Advances in fungal gene cluster diversity and evolution, Phylogenomics of Fusarium oxysporum species complex, Phylogenomic analyses of pathogenic yeasts, and the Phylogenetics and phylogenomics of rust fungi. The series continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines, critically analyzing future directions.